Atividades de autocuidado de pacientes com diabetes mellitus tipo 2 em seguimento ambulatorial de um hospital universitário - Larré, Mariana Costa (2017)
Quantitative study, descriptive and transversal aimed to analyze the activities of self-care of patients with a diagnosis of Diabetes Mellitus type 2 (DM2) in follow-up at the outpatient clinic of the University hospital of the Federal University of Sergipe. Data collection occurred from February to May 2016. Sample was non-probability for convenience type consists of 163 patients with DM2. Data were collected through a questionnaire related to the demographic data and the other pertaining to the Activities of Self-care with Diabetes, both applied as a form of personal interview. For the analysis of the data was performed descriptive statistics and calculate the mean and standard deviation for each item of the six dimensions of Self-care Activities Questionnaire with Diabetes. With regard to socio-demographic variables, it was observed that the average age of the participants was 62,99 years. There was a predominance of females with 104 (63,8%) women. With regard to schooling, 92 (56,5%) individuals reported incomplete elementary education. About the occupation, 93 (57,0%) participants were retired. The monthly household income revealed average real 1.355,75. Regarding the clinical variables, participants presented average of 15,8 years from time of diagnosis of DM2. Most patients, 32 (19,6%), the restricted diet, practiced physical activity and used the oral antidiabetic and insulin. 87 (69,0%) people use, such as oral antidiabetic, only Metformin Hydrochloride. About comorbidities, hypertension with 135 (82,8%) people and dyslipidemia with 110 (67,5%) participants. With regard to glycated hemoglobin, 107 (65,6%) participants presented values greater than or equal to 7%. Regarding the self-care activities developed by the patients, in the dimensions on general and specific feeding, the majority of the individuals had a desirable self-care behavior. On the other hand, the dimension on physical activity had an undesirable self-care behavior. Regarding the dimension on blood glucose monitoring, on the item on the frequency of blood sugar assessment and on the item on the blood sugar assessment in the number of times recommended by a health professional, the majority of the participants showed a behavior of Undesirable self-care. Regarding the dimension regarding foot care, in the item regarding examining the feet, most individuals showed an undesirable self-care behavior. On the item examine the inside of the shoes before putting them on and on the item on drying the interdigital spaces after washing the feet most of the subjects presented a desirable self-care behavior. In the dimension on the use of the medication most of the individuals had a desirable self-care behavior. It was evidenced that 153 (93,9%) users had not smoked in the last seven days. Of these, 111 (68,1%) reported never having smoked. In front of the findings was possible to analyze the activities of self-care of individuals with DM2. It is expected that these results may contribute to the nurse in the preparation of educational measures, with a focus on self-care of patients with DM2 and, consequently, help to improve the quality of life of these individuals.